THE EFFECT OF THE IMPLEMENTATION OF GOOD UNIVERSITY GOVERNANCE AND THE INTERNAL CONTROL SYSTEM ON THE QUALITY OF FINANCIAL STATEMENTS WITH ACHIEVEMENT MOTIVATION AS A MODERATING VARIABLES (Survey on Perguruan Tinggi Swasta Kota dan Kabupaten Bandung) - Fatimah Nurjannati Iskandar (Cross-border, 2022)
The purpose of this study was to determine the effect of implementing good university governance and internal control systems on the quality of financial reports, with need for chievement motivation as a moderating variable. The research method used in this study is an explanatory method, which is research that proves the existence of cause and effect and the relation that affects or is affected by two or more variables studied (Sekaran, 2013). The object of this research is the finance department and financial staff at private universities in Bandung city and Bandung district, with a total of 100 respondents. The results show that: (1) good university governance affects the quality of financial reports, (2) the internal control system affects the quality of financial reports, and (3) achievement motivation weakens the relationship between good university governance and the internal control system and the quality of financial reports. In other words, achievement motivation does not act as a moderating variable. Then the authors propose that to improve good university governance, private universities should do things related to management transparently, which is by conducting socialization to the academic community, especially the finance department. In addition, private universities are expected to be able to provide information to the public through the university's website. Through this, private universities are able to improve the internal control system, as well as minimize and monitor various forms of irregularities in private universities. Furthermore, to increase the achievement motivation of private universities, universities should provide rewards or awards for employees who have achievements in work, as well as provide opportunities for the finance department to attend several professional education and certified trainings. This can help the finance department keep up with developments in the business world and technological changes, because the business world is always experiencing rapid development. The financial department should improve the quality of the financial reports of private universities by submitting financial reports and asking supervisors to review them in stages, before they are reported. In addition, the preparation of financial reports must be presented in accordance with the regulations applicable to each of private universities.